Nordeste Semiárido, semidramático: uma análise do cotidiano do semiárido na Revista Nordeste - Lopes, Poliana Souza de Queiroz (2013)
The present study aimed to understand how journalism shapes Brazilian semi-arid Region (Northeast Region), based on the review of reports published in Nordeste (Northeast) Magazine. The choice for the analysis of this magazine was to be able to identify how this press media, which is produced in the northeast regional limits, deals with the semiarid. For that, this research had a corpus made of 12 copies of the magazine, published during the period from January to December of the year 2012. The choice of empirical clipping allowed us to investigate how this magazine talks about the region throughout the year. The theoretical reflections followed a path of approach that included a bibliographical survey about the semiarid region in Northeast, considering both its historical and geographical configuration, as well as the discoursed weaved about this portion; of Everyday life as a style and of the journalist as a reality producer. The methodology used was the formist paradigm, from the social forms. Through this procedure, it was possible to surpass the ready and fixed models and to look to the deeper appearance of daily life. Forms of gender, language, sources and themes were used as categories of analysis.